Acute toxicity study of Andrographis paniculata (Burm.f) Ness herbs and Gynura procumbens (Merr) leaves extracts combination - Kurnia Rahayu Purnomo Sari; Nofran Putra Pratama; Nadia Husna (Jurnal Ilmiah Farmasi, 2020)
AbstractBackground: Development of medical plants as an alternative treatment needs support in terms of scientific evidence to increase public confidence to ensure the safety of its use. Recent research on Andrographis paniculata (Burm. f) Ness and Gynura procumbens (Lour.) Merr showed that the combination of these extracts has a potential to be developed into antihyperglycemic agent and there’s no any potential toxicity for each extract.Objective: The aim of this study was to evaluate the acute toxicity level of these two extracts combination. From this research, it is expected that information can be obtained regarding the safety of extracts to support the further development of the extract combination.  Method: The method that used in this research is based on OECD 423. Observation was intensively done to animal behavior 4 h after acute exposure and continued up to 14 days after acute exposure to evaluate whether there were animal died. After the 15 days, all the animals were sacrificed and the vital organ was isolated for histological study.Results: The results showed that the exposure of these combination didn’t caused any to toxicity symptoms and there’s no animals died. Histological study on hepar showed that there’s no mayor damage in the hepar even after exposure of 2000 mg/kgBW dose.Conclusion: The combination of ethanol extract of A. paniculata herbs and G. procumbens leaves was categorized as unclassified (>2000 mg/kgBW) in term of toxicity levels based on Globally Harmonized Classification System.Keywords: Andrographis paniculata (Burm.f) Ness, Gynura procumbens (Lour.) Merr, acute toxicityIntisariLatar belakang: Pengembangan tanaman obat sebagai alternatif pengobatan perlu dukungan dari segi scientific evidence untuk meningkatkan kepercayaan masyarakat dan menjamin keamanan penggunaannya. Penelitian terbaru tentang sambiloto dan sambung nyawa menunjukkan bahwa kombinasi ekstrak tersebut berpotensi untuk dikembangkan menjadi agen antihiperglikemia dan dibutuhkan pemastian keamanannya.Tujuan: Penelitian bertujuan untuk mengevaluasi potensi ketoksikan secara akut kombinasi ekstrak larut etanol herba sambiloto dan daun sambung nyawa.Metode: Metode yang digunakan pada penelitian ini mengacu pada panduan OECD 423. Pengamatan yang dilakukan termasuk pada tingkah laku hewan uji tikus betina galur Wistar berjumlah 15 ekor, secara intensif terhadap gejala toksisitas selama 4 jam awal setelah paparan sediaan uji kemudian dilanjutkan hingga 14 hari pasca paparan untuk melihat ada/tidaknya hewan uji yang mati. Pada hari ke-15, seluruh hewan uji dikorbankan dan dibedah untuk diisolasi, ditimbang organ vitalnya dan dilakukan pengamatan histologi. Hasil: Hasil penelitian menunjukkan bahwa kombinasi ekstrak tersebut tidak menyebabkan gejala toksik terhadap hewan uji dan tidak ada satupun hewan uji yang mati. Hasil histopatologi organ hepar menunjukkan bahwa kombinasi ekstrak ini tidak menunjukkan efek berbahaya pada organ hepar hewan uji yang telah diberi paparan akut dengan dosis 2000 mg/kgBB. Kesimpulan: Ketoksikan kombinasi ekstrak larut etanol herba sambiloto dan daun sambung nyawa masuk dalam kategori unclassified (>2000mg/kgBB) menurut Globally Harmonized Classification System.Kata kunci : Andrographis paniculata (Burm.f) Ness, Gynura procumbens (Lour.) Merr, toksisitas akut